CRITICAL FACTORS IN DEVELOPING SUSTAINABLE FOOD PACKAGING - Tirdasari, Nyayu Lathifah; Oktariani, Andina; Indrawan, Dikky; Hasanah, Nur (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The sustainability issue has pushed the food industry, continually looking for new materials to reduce and replace plastics in their packaging. However, the recent development of novel materials is still less satisfactory due to different involvement from different vital players such as government, society, and industry. This paper analyzed the critical success factors of new material development for food packaging based on different key players, involvements, and interests. A survey was conducted by the authors to gather information related to the development factors and the participation factors based on the three key players. This research employed descriptive quantitative design. This design allows research to collect and describe the found clusters and factors. The results revealed that the critical success factors are classified into five clusters, namely technical substitution, technical drivers/barriers, application barriers, cost barriers, and raw material supply barriers. Differently from developed countries, the critical vital players' participation, especially from the government, was essential in developing new material for food packages. Keywords: critical success factor, descriptive quantitative, food industry, food packaging, sustainability development goals